Acces To Justice Kesehatan Lingkungan dan Masyarakat Kabaena Sulawesi Tenggara Yang Terkena Dampak Pertambangan - Alikhan, La Ode Akbar (JURNAL HUKUM KESEHATAN INDONESIA, 2024)
the environmental health of Kabaena Island and the public health of Kabaena. This study aims to advocate for mining corporate to carry out their social and environmental responsibilities, advocate for both central and regional governments to conduct supervision and re-check related to AMDAL, and revoke company permits if there is maladministration in the issuance of mining IUPs operating on Kabaena Island and advocate for the Kabaena community regarding how legal remedies can be taken when there are losses due to mining on Kabaena Island. This study uses a normative research method, with data types in the form of secondary data, such as regulations, research journals, research reports and articles. The research findings indicate that mining that occurs on Kabaena Island causes environmental damage which results in the deterioration of the Kabaena environmental health and there are also people who are affected by ISPA and skin diseases due to the impact of mining. Therefore, this research encourages emphasis on corporate to carry out their social and environmental responsibilities, pressuring the Regional and Central Governments to supervise and review mining activities in Kabaena.